2023
DOI: 10.1007/s11060-023-04368-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up of patients with WHO grade 2 oligodendroglioma

Louise Carstam,
Francesco Latini,
Ole Solheim
et al.

Abstract: Purpose Since the introduction of the molecular definition of oligodendrogliomas based on isocitrate dehydrogenase (IDH)-status and the 1p19q-codeletion, it has become increasingly evident how this glioma entity differs much from other diffuse lower grade gliomas and stands out with longer survival and often better responsiveness to adjuvant therapy. Therefore, apart from using a molecular oligodendroglioma definition, an extended follow-up time is necessary to understand the nature of this slow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
4
4
0
Order By: Relevance
“…This study presents the largest patient cohort analysis on 1p19q-codeleted ODG WHO grade 2 conducted by a single institution to date, providing a comprehensive analysis of long-term outcomes and prognostic factors for survival. As detailed in Table 3 , the observed median PFS of 6.8 years and median OS of 18.4 years in our cohort are consistent with the favorable prognosis associated with this molecular subtype, consistent with previous studies [ 6 , 14 17 ]. Notably, these results are better compared to the 24.7 months of median PFS, and 50.8 months of median OS reported in our recent study involving 95 patients with anaplastic ODG at our institution [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study presents the largest patient cohort analysis on 1p19q-codeleted ODG WHO grade 2 conducted by a single institution to date, providing a comprehensive analysis of long-term outcomes and prognostic factors for survival. As detailed in Table 3 , the observed median PFS of 6.8 years and median OS of 18.4 years in our cohort are consistent with the favorable prognosis associated with this molecular subtype, consistent with previous studies [ 6 , 14 17 ]. Notably, these results are better compared to the 24.7 months of median PFS, and 50.8 months of median OS reported in our recent study involving 95 patients with anaplastic ODG at our institution [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study presents the largest patient cohort analysis on IDH-mutant, 1p19q-codeleted ODG WHO grade 2 conducted by a single institution to date, providing a comprehensive analysis of long-term outcomes and prognostic factors for survival. As detailed in Table 3, the observed median PFS of 6.8 years and median OS of 18.4 years in our cohort are consistent with the favorable prognosis associated with this molecular subtype, consistent with previous studies [6, [14][15][16][17]. Notably, these results are better compared to the 24.7 months of median PFS, and 50.8 months of median OS reported in our recent study involving 95 patients with anaplastic ODG at our institution [18].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported contrast enhancement in 25 to 56% of patients with lower grade ODG [14,17,[26][27][28], a range comparable to the 31.2% observed in our study. Several studies have also identi ed contrast enhancement on MRI scans as a potential prognostic factor in IDH-mutant gliomas [14,26,29].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations